TEACHERS' PEDAGOGICAL BELIEFS, KNOWLEDGE AND CLASSROOM TEACHING PRACTICES: A CASE STUDY OF TEACHING ENGLISH AS A FOREIGN LANGUAGE AT UNIVERSITY LEVEL - Susanti, - (2015)
This research reports the teachers' pedagogical beliefs, knowledge and their teaching approaches to EFL (English as a Foreign Language) instructions. The study was conducted to answer the questions: What are the common pedagogical beliefs do teachers have regarding their approaches to EFL instructions? and, in what ways do their pedagogical beliefs match with their teaching practices in the classroom? This study is a case study in its nature which combines quantitative and qualitative data for the analysis. Questionnaire, interviews, classroom observations, and documents analysis were used to describe teachers' pedagogical beliefs and how the beliefs were practiced in the actual classroom teaching practices. The result revealed that the teachers had common beliefs regarding the conception of teaching and learning English as a foreign language. Similar beliefs i.e.: Language learning aptitude, Difficulty of language learning, Nature of language learning, Language learning and communication strategies, and Language learning and motivation were also shared among the teachers. A variation of approaches to EFL instructions was found in the ways the teachers translate their beliefs in the teaching practices. However, inconsistencies between their approaches and practices were also found. This study is hoped to be significant for both theoretical and practical considerations in Indonesian EFL context.